2020
DOI: 10.1002/jpen.1814
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Residual to Predict Necrotizing Enterocolitis in Preterm Piglets As Models for Infants

Abstract: Background Necrotizing enterocolitis (NEC) is a serious intestinal inflammatory disease in preterm infants. High volume of gastric residual (GR) after oral feedings is often used as a predictor of NEC, but evidence is limited. Using NEC‐sensitive preterm piglets as models, we hypothesized that GR mass and related plasma biomarkers predict early onset of NEC. Methods In total, 258 newborn preterm piglets were fed bovine milk–based formulas for 5 days. At euthanasia, the stomach, small intestine, and colon were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 46 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…The preterm piglet model has been used to study gut maturation and necrotizing enterocolitis (NEC) in relation to diet. Recently, it was shown that aspects of feeding tolerance can also be evaluated in this model, using gastric residual measurements and X-ray contrast imaging [21].…”
Section: Introductionmentioning
confidence: 99%
“…The preterm piglet model has been used to study gut maturation and necrotizing enterocolitis (NEC) in relation to diet. Recently, it was shown that aspects of feeding tolerance can also be evaluated in this model, using gastric residual measurements and X-ray contrast imaging [21].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the severity of NEC in piglets has been assessed using gross injury scoring which depicts macroscopic damage of the intestine, or histologic injury scoring, or a combination of both ( 18 , 24 26 , 29 31 , 37 , 59 , 61 63 , 65 , 68 ). During our study, it was common to find piglets with high gross injury and high histologic injury scores that appeared clinically healthy throughout the entire experiment and did not show bacterial translocation to internal organs.…”
Section: Discussionmentioning
confidence: 99%
“…We used preterm piglets as a model for preterm infants because they show many similarities to infants in their complications after preterm birth, including maldigestion, poor respiration, brain defects, high NEC sensitivity and a degree of feeding intolerance with large gastric residuals (16,20,33,34). The model has translational limitations, not only because preterm piglet anatomy and physiology may differ from infants (e.g., a relatively long small intestine and high NEC sensitivity) but also because serial X-rays are required to accurately assess the passage of contrast through the entire gut.…”
Section: Discussionmentioning
confidence: 99%